MATHEMATICAL AND ALGORITHMIC MODELS OF INFORMATION PROCESSING AND MANAGEMENT SYSTEMS - Kenzhebaeva Zh.E,; Baynazarova R.M., (Academic Journal of Physical and Chemical Sciences, 2019)
The article presents mathematical and algorithmic models of information processing and control systems. The algorithm should be standardized for all permissible input data, since the development of an algorithm is a process that is quite creative, therefore it requires significant costs and time and mental effort, and therefore, it is preferable that it provides a solution to unique tasks and developed to solve one problem. Regarding the purpose of information models, it is often in obtaining data to achieve the best performance indicators of a modeling object that can be used to prepare and make decisions of an economic, social, organizational or technical nature. Mathematical models consider many different functional dependencies, however, the main problem of modern systems for constructing mathematical models is still obtaining analytical equations describing the dynamics of the system under study.